Comparative analysis of hepatocellular carcinoma in men and dogs - Grabarević, Željko (Array, 2009)
Abstract: Concerning the important differences in the ethiopathology of hepatocelular carcinomas (HCC) in humans and dogs, our work describes the expression of epidermal growth factor receptor (EGFr), cytokeratine 19 (CK19), vascular endothelial growth factor (VEGF) and transforming growth factor beta receptor (TGFb-r) in tumors arising in both species. Investigation included 25 cases of human and 8 cases of dog tumors. All human cases were noted in cirrhotic livers, while in dogs the tissue adjacent to tumor was not changed. In humans in two cases hepatitis B virus (HBV) and in one case hepatitis C virus (HCV) were determined. Investigation showed lack of TGFb-r reaction in six cases of canine HCC, while in humans only one case was negative. In most tumors specific hepatocyte antigen Hepatocyte Paraffin 1 marker (Hep Par 1) was mainly positive with markedly decreased reaction compared to the normal hepatocytes, while cytokeratine 19 for billiary epithelium was negative. The result of our investigation rise the question about the possible role of tumor suppressor gene TGFb-r in the development of HCC in dogs and in the same time emphasizes its importance in human diseases